2012
DOI: 10.1002/ijc.27682
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD8 T‐cell responses restricted to multiple HLA class I alleles in a cancer patient by immunization with a 20‐mer NY‐ESO‐1f (NY‐ESO‐1 91‐110) peptide

Abstract: Immunogenicity of a long 20-mer NY-ESO-1f peptide vaccine was evaluated in a lung cancer patient TK-f01, immunized with the peptide with Picibanil OK-432 and Montanide ISA-51. We showed that internalization of the peptide was necessary to present CD8 T-cell epitopes on APC, contrasting with the direct presentation of the short epitope. CD8 T-cell responses restricted to all five HLA class I alleles were induced in the patient after the peptide vaccination. Clonal analysis showed that B*35:01 and B*52:01-restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…From the 114 studies, full-text was unavailable for one study 13 , 2 studies were duplicates published under different titles 14,15 , one study only described the study design 16 and 6 studies did not report safety, tolerability and/or toxicity results 7,[17][18][19][20][21] . These together with 11 case reports [22][23][24][25][26][27][28][29][30][31][32] and 2 letters to the editor were excluded 33,34 . Ultimately, a total of 91 studies were included in the systemic safety review.…”
Section: Resultsmentioning
confidence: 99%
“…From the 114 studies, full-text was unavailable for one study 13 , 2 studies were duplicates published under different titles 14,15 , one study only described the study design 16 and 6 studies did not report safety, tolerability and/or toxicity results 7,[17][18][19][20][21] . These together with 11 case reports [22][23][24][25][26][27][28][29][30][31][32] and 2 letters to the editor were excluded 33,34 . Ultimately, a total of 91 studies were included in the systemic safety review.…”
Section: Resultsmentioning
confidence: 99%
“…Like other translocation-driven cancers, synovial sarcoma demonstrates a relative paucity of nSSMs (12), which likely explains its unresponsiveness to checkpoint blockade (13). In contrast, 70% to 80% of synovial sarcomas express NY-ESO-1 (14)(15)(16), an immunogenic cancer testis antigen that has been targeted using vaccines (17)(18)(19)(20)(21) and adoptive transfer of T cells engineered to express NY-ESO-1 c259 , an affinity-enhanced T-cell receptor (TCR) targeting NY-ESO-1/LAGE1a (22)(23)(24)(25).…”
Section: Significancementioning
confidence: 99%
“…17,37 In that regard, numerous publications have reported on the immunogenicity of NY-ESO-1, and in particular of the protein region 87-111. 17,18 , 20,38 Mandic et al previously reported on the characterization of a CD4 T-cell clone recognizing the epitope 87-101 presented by HLA-DR7 transfected cells, 17 By fine mapping of specific CD4 C T-cell responses in our cohort of HLA-DR7…”
Section: E1216290-8 P Baumgaertner Et Almentioning
confidence: 82%